Implementasi Arsitektur Operational Data Store (ODS) dan Dimensional Data Store (DDS) dalam Pembangunan Data Mart Lulusan - Rohmana Zulfa Bakhtiar; Slamet Riyadi; Asroni Asroni (Semesta Teknika, 2015)
Universitas Muhammadiyah Yogyakarta (UMY) is a big and high-grade educational institution. During the period of 1998-2014, UMY has produced about 20550 graduates. But, the big number of graduates is not supported by a good data storage system. Whereas those data are needed in filling up the accreditation form. For that reason, we have to build an integrated data storage system to provide graduates data as needed, that is graduate data mart. The development of graduate data mart uses SDLC Model Waterfall method. This method involves several types, there are requirement analysis, design system, implementation system, testing system, and maintenance system and those must be done sequentially. If there is an error, the process must be repeated from the beginning to fix the error. Development of graduate data mart uses Operational Data Store (ODS) and Dimensional Data Store (DDS) architecture. Those architectures are selected because they support transactional level. By using those architectures, graduate data mart is capable to display the data of graduates on the academic year, GPA, educational years, and the status of the student transfers. As the result, those data are able to help the management of university in filling up the accreditation form.